Floral structure, development of the gynoecium, and embryology in schinopsis balansae engler (anacardiaceae) with particular reference to aporogamy - González, Ana María (2016)
Fil: González, Ana María. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.